Cyberchondria scale (CS): Development, validity and reliability study - Durak Batıgün, Ayşegül; Gör, Nağme; Kömürcü, Burcu; Ertürk, İpek Şenkal (My University, 2018)
Objective: The aim of the current study is to develop culture specific, multidimensional and self-report Cyberchondria Scale (CS) which can be used to evaluate one’s emotional, cognitive and behavioral tendency to cyberchondria and to determine the psychometric properties of this scale. Method: The study was conducted with two different samples consisted of Internet users. To investigate the factor structure, the first sample was composed of 250 (49.6% women, 50.4% men) individuals aged between 18 and 65. The second sample in which confirmatory factor analysis (CFA) was conducted consisted of 360 (61.1% women, 38.3% men) individuals aged between 18 and 65. In addition to CS, Internet Addiction Scale (IAS), Brief Symptom Inventory (BSI) and Health Anxiety Inventory (HAI) were used in this study. Results: The exploratory and CFA revealed a five-factor structure called “Factors Increasing Anxiety”, “Compulsion/Hypochondria”, “Factors Decreasing Anxiety”, “Doctor-Patient Interaction”, “Dysfunctional Internet Use”. The model obtained by CFA represented acceptable goodness of fit values and other reliability and validity values were found to be satisfactory. Conclusion: CS could be evaluated as a valid and reliable scale which would be used in clinical and health psychology studies conducted in Turkey.

Amaç: Bu çalışmanın amacı, bireyin siberkondriyaya ilişkin duygusal, bilişsel ve davranışsal yatkınlığını değerlendirmede kullanılabilecek kültürümüze özgü, çok faktörlü, öz bildirime dayalı bir Siberkondriya Ölçeği (SİBKÖ) geliştirmek, geliştirilen bu ölçeğin psikometrik özelliklerini belirlemektir. Yöntem: Çalışma, İnternet kullanabilen iki ayrı örneklem grubuyla yürütülmüştür. Ölçeğin faktör yapısının belirlendiği ilk örneklem grubunu, yaşları 18-65 arasında değişen 250 (%49.6’sı kadın, %50.4’ü erkek) kişi oluşturmuştur. Ölçeğin doğrulayıcı faktör analizinin (DFA) gerçekleştirildiği ikinci örneklem grubunu ise 18-65 yaş arasında 360 (%61.1’i kadın, %38.3’ü erkek) kişi oluşturmuştur. Çalışmada SİBKÖ’nün yanı sıra, İnternet Bağımlılığı Ölçeği (İBÖ), Kısa Semptom Envanteri (KSE) ve Sağlık Anksiyetesi Envanteri (SANKE) kullanılmıştır. Bulgular: Yapılan açımlayıcı ve DFA sonucunda, “Kaygıyı Artıran Faktörler”, “Kompulsiyon/Hipokondri”, “Kaygıyı Azaltan Faktörler”, “Doktor-Hasta Etkileşimi” ve “İşlevsel Olmayan İnternet Kullanımı” olarak adlandırılan beş faktörlü yapı elde edilmiştir. DFA’da elde edilen model uyum indekslerinin kabul edilebilir sınırlar içinde olduğu görülmüş; elde edilen diğer geçerlik ve güvenirlik değerleri de uygun bulunmuştur. Sonuç: SİBKÖ, Türkiye’de yürütülen klinik psikoloji ve sağlık psikolojisi alanındaki çalışmalarda kullanılabilecek, geçerli ve güvenilir nitelikte bir ölçek olarak değerlendirilebilir.
Siberkondriya ölçeği (Sibkö): Geliştirme, geçerlik ve güvenirlik çalışması
Keywords: Cyberchondria Scale; Reliability; Validity; Siberkondriya Ölçeği; Güvenirlik; Geçerlik